Історична ґенеза відповідальності в органах внутрішніх справ: трудоправовий аспект - Гончарук, В. В.; Honcharuk, V. V.; ORCID: http://orcid.org/0000-0002-8157-0130; ResearcherID: J-7912-2016 (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 3 (70). - С. 180-190., 2015)
Наголошено, що формування органів внутрішніх справ України у післяжовтневий період відбувалося у надзвичайно складних умовах. Детально охарактеризовано і проаналізовано затверджений наприкінці 1923 року Дисциплінарний статут робітничо-селянської червоної міліції. Визначено, що на основі встановлених державою суворих правил службового етикету та атрибутики, які поширювалися не тільки на службову діяльність працівників, а і на їхню поведінку поза службою, вимоги до працівників міліції в той час були значно суворіші, ніж вимоги до трудової дисципліни, що висувалися до працівників позавідомчих організацій.

It is emphasized that the formation of Internal Affairs Agencies of Ukraine in the post-October period was in extremely difficult conditions. The duties for organization and formation of the agencies were laid on various institutions under the leadership of local councils and revolutionary committees that had no elaborated legislation, which would regulate the common principles of organization and activities. In the beginning of 1919 the People’s Commissariat of Internal Affairs was created as a part of the Council of People’s Commissars of Ukraine, which began to develop the regulatory basis of internal affairs agencies’ activities. The Disciplinary Regulations of the workers’-peasants’ red militia approved at the end of 1923 was characterized and analyzed in details. The Regulations conferred the rights and responsibilities of militia chiefs and their subordinates, defined the types of rewards and punishments for officers. Analysis of the formation and transformation of the regulatory basis of labor and legal liability of the officers of Internal Affairs Agencies of Ukraine confirms that, despite the changes of historical and political conditions of the internal affairs agencies’ activities, the service and labor discipline of the officers has been always based on a strict unity of command and has differed by the nature of power and subordination, has demanded unconditional compliance with the rules and regulations set by the laws and other regulations, has stipulated the use of special disciplinary measures of impact on the officers, who allowed deviation from its requirements, providing the chiefs of the agencies, institutions and units the wide range of disciplinary power. It is emphasized that through the established by the state strict rules of service etiquette and paraphernalia that have been spread not only on the service activities of the officers, but also on their behavior out of service, its requirements for militia officers at the time were much more stringent than the requirements for labor discipline put forward for the employees of non-departmental organizations.

Отмечено, что формирование органов внутренних дел Украины в послеоктябрьский период происходило в чрезвычайно сложных условиях. Подробно охарактеризован и проанализирован утверждённый в конце 1923 года Дисциплинарный устав рабоче-крестьянской красной милиции. Определено, что на основе установленных государством строгих правил служебного этикета и атрибутики, которые распространялись не только на служебную деятельность работников, но и на их поведение вне службы, требования к работникам милиции в то время были значительно строже, чем требования к трудовой дисциплине, которые предъявлялись к работникам вневедомственных организаций.
Goncharuk, V.V. (2015), “The historical genesis of the liability within internal affairs agencies: labor and legal aspect” [“Istorychna geneza vidpovidalnosti v orhanakh vnutrishnikh sprav: trudopravovyi aspekt”], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 3, pp. 180-190.
Гончарук, В. В. Історична ґенеза відповідальності в органах внутрішніх справ: трудоправовий аспект // Вісник Харківського національного університету внутрішніх справ. - 2015. - № 3 (70). - С. 180-190.
Гончарук В. В. "Історична ґенеза відповідальності в органах внутрішніх справ: трудоправовий аспект." Вісник Харківського національного університету внутрішніх справ 3 (2015): 180-190.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; відповідальність; робітничо-селянська міліція; кадрове забезпечення; трудоправовий аспект; Internal Affairs Agencies; liability; workers’-peasants’ militia; staffing; labor and legal aspect; органы внутренних дел; ответственность; рабоче-крестьянская милиция; кадровое обеспечение; трудоправовой аспект; історія; история; staffing system